Synergistic effects of recombinant AGAAN antimicrobial peptide with organic acid against foodborne pathogens attached to chicken meat - Jiddah, Nafiu Usman; Ajingi, Yau Sabo; Rukying, Neeranuch; Rattanarojpong, Triwit (National Nutrition and Food Technology Research Institute, 2024)
Background and Objective: Fresh chicken meat includes the capacity to contain foodborne pathogens. A previous study has demonstrated efficacy of recombinant AGAAN antimicrobial peptide against various bacterial strains. In general, AGAAN is a newly discovered antimicrobial peptide with a unique cationic alpha-helical structure. The peptide is originated from the skin secretions of Agalychnis annae. This peptide showed a significant affinity towards the negatively-charged microbial lipid bilayer, as previously demonstrated by the experimental and in-silico analyses. However, the major concerns include high production costs, limited expression, laborious process and potential toxicity associated with concentrated peptides. In this research, the synergistic effects with organic acid were addressed to decrease these problems while preserving its bactericidal activity. Material and Methods: Recombinant AGAAN and organic acids were assessed on Staphylococcus aureus ATCC 6538 and Escherichia coli ATCC 8739. This was carried out by assessing minimum inhibitory concentration and fractional inhibitory concentration. In addition, effects of the combination on bacterial membrane integrity by carrying out beta-galactosidase assessment. Additionally, the potential efficacy of this combination in preserving poultry meat was investigated. Results and Conclusion: Minimum inhibitory concentration of the recombinant AGAAN against the two bacterial strains was 0.15 mg.ml-1. In contrast, the minimum inhibitory concentration of acetic acid against Staphylococcus aureus and Escherichia coli were 0.2 and 0.25% v v-1, respectively. The combination demonstrated significant synergy, as evidenced by fractional inhibitory indices of 0.375 against the two foodborne pathogens. Based on the study, the combination effectively inhibited proliferation of these disease-causing microorganisms that led to foodborne illnesses within 300 min. Presence of intracellular beta-galactosidase indicated that the combination of factors has caused damages to the cell membrane, resulting in its compromised integrity. Red blood cells exposed to various concentrations of recombinant AGAAN and acetic acid did not result in hemolysis. Results showed significant differences (p < 0.05) in all the experiments on meat samples that received treatments with recombinant AGAAN and acetic acid. The current study detected that a combination of recombinant AGAAN antimicrobial peptide with organic acid could effectively inhibit growth of pathogens at lower concentrations. Data presented in this study can help food industries develop further efficient cost-effective antimicrobial uses.